Pengembangan E-LKPD Interaktif Berbasis Wizer.me dalam Pembelajaran Pendidikan Pancasila di MINU Waru 1 Sidoarjo - Zuhriah, Amillatuz; Taufik; Erfansyah, Nasrul Fuad; Juhaeni (Faculty of teaching training and education, 2025)
This research aims to answer the challenges in learning Pancasila education by developing interactive E-LKPD based on wizer.me. Through the application of the ADDIE development model and involving experts, this product has been successfully developed and validated. The interactive E-LKPD obtained validation from material experts of 84% and media experts of 88.57%, both of which were in the